Forecasting biotoxin contamination in mussels across production areas of the Portuguese coast with Artificial Neural Networks - Cruz, Rafaela C. (2022)
Funding Information: The work was also supported by national funds through Fundação para a Ciência e a Tecnologia (FCT), Portugal with references CEECINST/00102/2018 and UID/Multi/04326/2020 (CCMAR). Publisher Copyright: © 2022 The Author(s)